2008
DOI: 10.1590/s1519-69842008000400007
|View full text |Cite
|
Sign up to set email alerts
|

Barn owl (Tyto alba) predation on small mammals and its role in the control of hantavirus natural reservoirs in a periurban area in southeastern Brazil

Abstract: The aim of this study was to inventory the species of small mammals in Uberlândia, Minas Gerais, Brazil, based on regurgitated pellets of the barn owl and to compare the frequency of rodent species in the diet and in the environment. Since in the region there is a high incidence of hantavirus infection, we also evaluate the importance of the barn owl in the control of rodents that transmit the hantavirus. Data on richness and relative abundance of rodents in the municipality were provided by the Centro de Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
2
11
0
8
Order By: Relevance
“…Because they represent the base of the trophic web for most of the large and medium vertebrates, small terrestrial mammals suffer a high risk of predation (e.g. Juarez and Marinho-Filho, 2002;Magrini and Facure, 2008;Sousa and Bager, 2008;Abreu et al, 2010). Additionally, anomalous colouration tends to strongly reduce the survival of these organisms, since these deficiencies make them visible to predators (Sazima and Di-Bernardo, 1991;Parsons and BonderupNielsen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Because they represent the base of the trophic web for most of the large and medium vertebrates, small terrestrial mammals suffer a high risk of predation (e.g. Juarez and Marinho-Filho, 2002;Magrini and Facure, 2008;Sousa and Bager, 2008;Abreu et al, 2010). Additionally, anomalous colouration tends to strongly reduce the survival of these organisms, since these deficiencies make them visible to predators (Sazima and Di-Bernardo, 1991;Parsons and BonderupNielsen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Another attractive attribute is the fact that small mammals, especially rodents, are the main prey source of barn owls and its diet is an accurate reflection of the local fauna composition as well as population fluctuations of prey (Alvarez-Castaneda et al, 2004;Tores et al, 2005;Granjon & Traore 2007;Magrini & Facure, 2008;Charter et al, 2009). Despite barn owls' relatively smaller size, their high metabolic rate enables them to exhibit a relatively high consumption rate, and are reported to feed up to one fourth of their body weight in prey daily (Marti et al, 2005).…”
Section: Why Barn Owls Are So Frequently Considered As Biological Rodmentioning
confidence: 99%
“…Most authors who have compared inventories of small mammals through pellets analysis and through conventional trapping have concluded that those methods were complementary (Bonvicino and Bezerra 2003, Scheibler and Christoff 2007, Magrini and Facure 2008, Rocha et al 2011. Thus, our results cannot be taken as an inventory of the non-volant small mammals living in the grassy savannas, marshes, and shrublands around Sinnamary.…”
Section: Weightmentioning
confidence: 87%